Apllication of Six Sigma and FMEA Methods to Improve The Quality of Laminated Tube Packaging - Hafizh Hazmi Al Fauzi; Rizqi Novita Sari (Yayasan Kita Menulis, 2025)
PT Lamipak Primula Indonesia is a company that produces various packaging made of plastic. The main product of PT Lamipak Primula Indonesia is toothpaste laminated tube packaging. PT Lamipak Primula Indonesia wants to minimize defects in products to minimize waste, reduce costs, increase efficiency, and maximize profits. This can also increase customer confidence in the product. PT Lamipak Primula Indonesia improves the quality of its products by applying Six Sigma with the DMAIC method. In this study, DPMO of 15766 was obtained and then converted to a sigma level of 3.7 which shows that the sigma level is below the 6 sigma level. This shows the achievement of sigma that has not been consistent and still shows the need for quality improvement in the laminated tube packaging production process in order to achieve zero defects. Based on FMEA analysis, it shows that the most significant failure occurs in machine conditions that cause defective shoulders with a value RPN of 210. This failure is caused by the lack of regular machine inspection, by the machine not being supervised in realtime, not following the SOP and the lack of worker skills.